International Financial Reporting Standards (IFRS) and Financial Performance of Multinational Companies in Nigeria: Array - Osho, Augustine; Olutayo, Moyinoluwa Esther; Olayinka, Emmanuel-Adeyefa (The Journal of Accounting and Management, 2021)
This study examined the relationship between International Financial Reporting Quality and the financial performance in the context of listed multinational companies in the Nigerian Stock Exchange (NSE) with the use of cross-sectional, time-series data, and OLS regression techniques. Also, some control variables were introduced in order to reduce omitted variable bias. Nine (9) multinational companies were concentrated upon between the period of 2012 and 2020 (9 years). The finding in this paper indicates that the extent of corporate disclosure is significantly associated with financial performance because it showed a positive correlation and significant result. The study concludes that, the more company complies with IFRS disclosure guidelines, the more the investors are attracted to investing in such company and thereby improving their financial performances (return on capital employed). The study recommended that among other things, companies should also be concerned with the disclosure of relevant information at a possible minimal cost to stabilize the possible positive effect of mandatory and voluntary disclosure of financial performance.